MUSIK ROK SEBAGAI BENTUK KONSTRUKSI SOSIAL DALAM MEREFLEKSIKAN PERUBAHAN SOSIAL GENERASI MUDA - Alialamsyah Kusumadinata (Universitas Djuanda Bogor, 2012)
The main objective of this study was to determine the extent of rock music in the form of social construction reflecting social changes young people. The research method used a case study with a qualitative approach. The data were collected through participant observation, in-depth interviews, and a literature review. Determination of informants was done by snow balling (snowball) on the basis of the criteria on the younger generation who liked and interested in rock music. While the researchers observed in active for about a year (2010-2011). The results showed that the level of penetration of significant symbols in rock music at the secondary socialization process of the four informants produce diverse identities. Produce the identity of the informant first